The paradoxical effects of high work methods and work scheduling autonomy - Bipp, Tanja; Walczok, Marvin (Zeitschrift für Arbeits- und Organisationspsychologie, 2024)
Job autonomy is traditionally seen as a core job characteristic with positive effects on work outcomes. However, in today’s world of work, excessive levels of job autonomy have also been suggested to lead to demands with negative downstream effects. We investigated paradoxical effects of high levels of two autonomy facets with regard to work engagement. In an experimental vignette study (N = 228 German employees), we manipulated two autonomy facets in a 2×2 between-subject design (high vs. low work methods autonomy vs. work scheduling autonomy). We found evidence for paradoxical effects for one facet: High levels of work scheduling autonomy directly stimulated work engagement but led to higher levels of work intensification therefore also (indirectly) hindering work engagement. To our knowledge, our findings are the first to provide evidence of the simultaneous paradoxical effects of work scheduling autonomy and an explanation for detrimental effects on work engagement via the intensification of work.
Online veröffentlicht: May 24, 2024
Gesehen am 04.11.2024